2019
DOI: 10.30651/jqm.v3i2.2833
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and histopathological aspect of the liver, lung, and kidney in Malaria

Abstract: Malaria is an infectious disease with worldwide distribution. The symptom ranges from asymptomatic to severe malaria that could cause mortality. Sequestration and rosetting in the capillaries of several organs in combination with the host inflammatory and immune response could cause multi-organ dysfunction including brain, liver, lung, kidney, etc. This review is to summarize the clinical and histopathological aspect of the disease, especially in lung, liver, and kidney. The clinical importance of severe malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These results indicated that the EECS was effective in reducing plasma levels of SGOT and SGPT to the normal levels. The excessive hepatic enzymes were released by the injured hepatocytes due to malarial infection [ 53 ]. In this study, the necrosis and degraded cells in the liver were repaired by the administration of EECS followed by the reduction in plasma level of SGOT and SGPT.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the EECS was effective in reducing plasma levels of SGOT and SGPT to the normal levels. The excessive hepatic enzymes were released by the injured hepatocytes due to malarial infection [ 53 ]. In this study, the necrosis and degraded cells in the liver were repaired by the administration of EECS followed by the reduction in plasma level of SGOT and SGPT.…”
Section: Discussionmentioning
confidence: 99%
“…1 Malaria causes organ dysfunction such as liver, lung, and brain. 2 One of the dangerous sign of malaria is anaemia, hypoglycaemia detected from the blood test. 3,4 These conditions impact cognitive impairment in children and productivity in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired kidney function is characterized by increased levels of blood urea nitrogen (BUN) and creatinine ((Isa et al, 2013;Kalia et al, 2015). Kidney histology research in malaria shows acute tubular necrosis, glomerulonephritis, and interstitial nephritis (Akil, 2019;Koopmans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%